2014
DOI: 10.1186/1756-0500-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to decrease skin cancer risk in outdoor workers: update to a 2007 systematic review

Abstract: BackgroundOutdoor workers are at high risk of harmful ultraviolet radiation exposure and are identified as an at risk group for the development of skin cancer. This systematic evidence based review provides an update to a previous review published in 2007 about interventions for the prevention of skin cancer in outdoor workers.ResultsThis review includes interventions published between 2007-2012 and presents findings about sun protection behaviours and/or objective measures of skin cancer risk. Six papers met … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 37 publications
1
53
1
Order By: Relevance
“…Interventions that include a component of education, activities to influence knowledge, attitudes or behaviors, and environment changes or policy are most likely to be effective. Recent reviews 15,16 have also concluded that there is now sufficient evidence demonstrating the effectiveness of educational and multicomponent interventions in promoting positive sun protection habits among outdoor workers. Nevertheless, it is unclear whether such interventions will be equally useful for workers from all outdoor industries, and more evidence is needed among different occupation types, especially nonrecreational settings.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Interventions that include a component of education, activities to influence knowledge, attitudes or behaviors, and environment changes or policy are most likely to be effective. Recent reviews 15,16 have also concluded that there is now sufficient evidence demonstrating the effectiveness of educational and multicomponent interventions in promoting positive sun protection habits among outdoor workers. Nevertheless, it is unclear whether such interventions will be equally useful for workers from all outdoor industries, and more evidence is needed among different occupation types, especially nonrecreational settings.…”
mentioning
confidence: 95%
“…14 Multicomponent interventions have included diverse strategies such as the provision of wide-brimmed hats and sunscreen, education sessions and sun safety reminders, policy development, and role modeling to prompt sun safe behavior change among workers. [14][15][16] A number of studies have found that multicomponent interventions, including several of these strategies, improved the sun safe behaviors of outdoor workers. For example, the Pool Cool study (2001) integrated environmental changes such as shade provision as well as sun safety education, sunscreen provision, and incentives for sun safe workers.…”
mentioning
confidence: 99%
“…Systematic reviews and meta-analyses have found some of these interventions to be efficacious for specific populations (Horsham, Sendall, et al, 2014; Lin, Eder, & Weinmann, 2011; Rodrigues, Sniehotta, & Araujo-Soares, 2013; Saraiya, Glanz, et al, 2004; Williams, Grogan, et al, 2013). However, many of these interventions have two key limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Patient counseling should also emphasize the common perceptions regarding sunscreen use discussed by Chen and colleagues. In addition to counseling, health professionals may consider the provision of personal protection equipment, including sunscreen, which has been shown to be efficacious in increasing sunscreen use [7]. Further, when developing interventions to address sunscreen use among melanoma survivors, health promotion practitioners may consider developing tailored, theoretically grounded interventions addressing barriers, benefits, and attitudes regarding sunscreen use specific to melanoma survivors [8].…”
mentioning
confidence: 99%